1984
DOI: 10.1111/j.2042-7158.1984.tb06934.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive effects and biotransformation of nicorandil, a new antianginal agent, administered to rats by different routes: comparison with nitroglycerin and isosorbide dinitrate

Abstract: The effects of nicorandil, N-(2-hydroxyethyl)nicotinamide nitrate (ester), in reducing systemic blood pressure (SBP) in rats were studied in comparison with isosorbide dinitrate and nitroglycerin. The drugs were administered to pentobarbitone-anaesthetized rats by jugular vein (i.v.), portal vein (p.v.), intrajejunal (i.j.), intraperitoneal (i.p.) and subcutaneous (s.c.) routes. Nicorandil was absorbed rapidly through all routes, and caused marked hypotension dose-dependently. With isosorbide dinitrate and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Unlike conventional nitrates, orally administered nicorandil seems to be more resistant to metabolic breakdown in the liver, and therefore easily enters the systemic circulation. This results in a greater bioavailibility after oral dosing (Sakai et al, 1984). According to a previous experiment (Shiraki et a/., 1981), a bolus intravenous injection of nicorandil (300 pg/kg) in the anaesthetized dog caused a fall of systemic blood pressure over 60 min.…”
Section: Discussionmentioning
confidence: 94%
“…Unlike conventional nitrates, orally administered nicorandil seems to be more resistant to metabolic breakdown in the liver, and therefore easily enters the systemic circulation. This results in a greater bioavailibility after oral dosing (Sakai et al, 1984). According to a previous experiment (Shiraki et a/., 1981), a bolus intravenous injection of nicorandil (300 pg/kg) in the anaesthetized dog caused a fall of systemic blood pressure over 60 min.…”
Section: Discussionmentioning
confidence: 94%
“…The plasma concentration of nicorandil decline as mean values of apparent elimination half-life was 52±13 minutes for 20 mg oral doses (42). Investigation about pharmacokinetics of nicorandil proved that nicorandil was rapidly and extensively absorbed from the gastrointestinal tract and no extensive presystemic metabolism seemed to occurred (43, 44). Additionally, IPC was believed to be transient (lasting less than 3 hours) (45).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been thought that SG-86, a denitrated metabolite of nicorandil, is pharmacologically inactive, and that possesses little interest as the object of precise investigation in this field. However, it should be noted that SG-86 is a main metabolite of nicorandil in humans [6] as well as in animals [16,17,201. Indeed, nicorandil given orally to humans and animals is rapidly absorbed (C,,, 15-30 rnin), and gradually metabolized to SG-86, mainly in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…N-(2-hydroxyethyl)nicotinamide (SG-86) is a main metabolite of nicorandil [6,16,17,201, which has been reported to be pharmacologically inactive [9,16,17,241. Recently, we found that nicorandil enhances the vasodepressor responses not only to adenosine, but also those to vasoactive intestinal polypeptide and calcitonin gene-related peptide, partly through K ATP channel activation, in rats [ 15, 191.…”
Section: Introductionmentioning
confidence: 99%